Analisis Pengaruh Word of Mouth, Variasi Produk, dan Gaya Hidup Terhadap Keputusan Pembelian Pada Es Teh Indonesia di Surabaya - Putri Dhofitri, Cantika Rosmawati; Maduwinarti, Ayun; Pratiwi, Ni Made Ida (Research Journal of Social Science and Economics, 2025)
Es Teh Indonesia is a Food & Beverages company founded by Haidhar Wurjanto in 2018 by offering a variety of beverage products made from tea and combined with milk, various fruit flavors, and other flavours. The purpose of this study is to determine the effect of word of mouth, product variety, lifestyle on purchasing decisions at Es Teh Indonesia in Surabaya and to determine word of mouth, product variety, lifestyle influence simultaneously on purchasing decisions at Es Teh Indonesia in Surabaya. This type of research used is quantitative research. In collecting data, the technique used is non-probability sampling. The number of respondents in this study were 100 respondents. Data collection techniques in this study using Google Form. Based on the results of this study, it proves that product variety and lifestyle have a significant effect on purchasing decisions for Es Teh Indonesia in Surabaya. Meanwhile, word of mouth has an effect but not significant on purchasing decisions. Based on the results of this study, it shows that word of mouth, product variety, and lifestyle have a joint effect on purchasing decisions. Keywords: word of mouth, product variety, lifestyle, purchasing decisions